Spatial load forecasting using fuzzy logic technology / Azmir Aman - Aman, Azmir (2003)
This report describes the Fuzzy logic technology to fuse the available information for spatial load forecasting. The developed program is performed by Fuzzy Tech Version 5.12. Different approach in spatial load forecasting based on land usage load modeling has been used to improve the performance of distribution load forecasting. Fuzzy Logic is applied in this forecast to aggregate appropriate geographic information to formulate future load growth based on different anticipated scenarios. For the purpose of this project, the Mamdani type of fuzzy controller was used. The assessment of the program has been obtained after making a comparison of the target load. The performance of the developed is also discussed in this report. The proposed scheme can provide distribution planners other alternatives to aggregate their information for spatial load forecasting.